Plastic mulch film residues in agriculture: impact on soil suppressiveness, plant growth, and microbial communities. Issue 2 (12th February 2022) - Qi, Yueling; Ossowicki, Adam; Yergeau, Étienne; Vigani, Gianpiero; Geissen, Violette; Garbeva, Paolina
Abstract: Plastic mulch film residues have been accumulating in agricultural soils for decades, but so far, little is known about its consequences on soil microbial communities and functions. Here, we tested the effects of plastic residues of low-density polyethylene and biodegradable mulch films on soil suppressiveness and microbial community composition. We investigated how plastic residues in a Fusarium culmorum suppressive soil affect the level of disease suppressiveness, plant biomass, nutrient status, and microbial communities in rhizosphere using a controlled pot experiment. The addition of 1% plastic residues to the suppressive soil did not affect the level of suppression and the disease symptoms index. However, we did find that plant biomasses decreased, and that plant nutrient status changed in the presence of plastic residues. No significant changes in bacterial and fungal rhizosphere communities were observed. Nonetheless, bacterial and fungal communities closely attached to the plastisphere were very different from the rhizosphere communities with overrepresentation of potential plant pathogens. The plastisphere revealed a high abundance of specific bacterial phyla (Actinobacteria, Bacteroidetes, and Proteobacteria) and fungal genera ( Rhizoctonia and Arthrobotrys ). Our work revealed new insights and raises emerging questions for further studies on the impact of microplastics on the agroecosystems. Abstract : Plastic mulch film residues did not change soil suppressiveness level in short-term experiment but created a new niche "plastisphere" that harbors a distinct microbial community dominated by potential fungal pathogens.